Sustainable Bonuses: Sign of Corporate Responsibility or Window Dressing? - Kolk, Ans (Journal of business ethics, 2014)
Despite a strong plea for integrating sustainability goals into traditional corporate bonus schemes, a comprehensive implementation of these systems has been lacking until recently. This article explores four illustrative cases from the Netherlands, where several multinationals started to pioneer with sustainable bonuses in the past few years. The article examines the setups and the different elements of bonus programmes used, in terms of performance criteria (focusing in particular on external vs. internal benchmarking), their link to specific stakeholders, type and size of bonuses, target levels and transparency. While sustainable bonuses signal corporate awareness of responsibility vis-à-vis society and stakeholders, credibility varies considerably depending on these elements. Our case evidence sheds some light on the extent to which sustainable bonuses may be a credible sign of corporate responsibility or rather just another perverse mechanism meant to keep up bonus levels (window dressing). A definite assessment is hampered by the emergent state and lack of full transparency—while ‘justified’ by companies for competitive reasons, this raises questions. Insights are offered to appraise current and future systems and provide directions for further research.